The Concept of Al-Qur'an on The Students’ Competence of 21st Century (Study of the Jalalain And Al-Mishbah Interpretation on al-Alaq Verses 1-5) - Dewi Sri Utami (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract: Students’ competence is a skill that must be possessed/achieved by students after learning Al-Qur'an as a guide for those who are cautious, who have provided a lot of inspiration related to the concept of education, especially in the letter Al-Alaq verse 1-5. So the purpose of this study is to find out the content of the letter al-Alaq verse 1-5, to know the students’ competence concept of 21st century in the law of the national education system article no. 20 of 2003, and know what are the students’ competence on 21st century contained in the letter Al-Alaq verse 1-5. This study is a library study (library research) which is qualitative descriptive, which uses documentation and study literature techniques in data collection. While the data analysis method used is the Tahlily interpretation method. The results of this study that: First, the content of this letter is the command to read which is not only limited to the command of reading but also to study, describe, analyze, so that new knowledge arises such as: jurisprudence, Tauhid or Islamic theology, morality, and others. Secondly, as for the relevance of the letter Al-Alaq verse 1 - 5 with the National Education System Law, there is a correspondence with regard to student competencies, namely: critical thinking competencies and problem solving, collaboration, communication, and creativity. Third, the students’ competence of 21st century according to Al-Alaq verse 1-5 is that in the first verse alluding to creative competence, the first and third verses allude to critical thinking and solving problems. Keywords: Al-Qur'an Concept, Students’ Competence on 21st Century, Interpretation Study